Sistemática filogenética de Epyrinae (Hymenoptera, Bethylidae) - Colombo, Wesley Dondoni (2021)
Epyrinae are the second most diverse subfamily of Bethylidae, with approximately 950 described species and 13 valid genera, of which 12 are extant: Anisepyris Kieffer; Aspidepyris Evans; Bakeriella Kieffer; Calyozina Enderlein; Chlorepyris Kieffer; Disepyris Kieffer; Epyris Westwood; Formosiepyris Terayama; Holepyris Kieffer; Laelius Ashmead; Trachepyris Kieffer and Xenepyris Kieffer; and one is extinct: †Elektroepyris. Epyrinae have a complex taxonomic history and only in the last decade their monophyly has recovered. Due to the difficulty in delimiting Epyrinae, many generic taxa were consequently classified inappropriately. Studies revising the concept of the epyrine genera are necessary and crucial, but they have been neglected due to the difficulty in interpreting morphostructural diversity. As a solution, molecular data has been used to help elucidate the morphostructural impasses. In this dissertation, the diversity of Epyrinae is explored, both alphaxonomically and phylogenetically, through molecular and morphological data, and by reconstructing phylogenetic trees, under different optimization criteria (Maximum Parsimony, Bayesian Inference and Maximum Likelihood). Additionally, the subfamily's paleodiversity was revised and, at the end, the Epyrinae were organized and redefined and the evolution of their lineages discussed. This thesis consists of four chapters, the first three of which aimed to explore and list the morphological and molecular patterns of the Epyrinae, providing data and information for the last chapter, which aimed to test the monophyly of the Epyrinae genera. In Chapter 1, an alpha-taxonomic review of Epyrinae from Papua New Guinea is present, exploring and listing morphological patterns and filling in gaps in Old World taxonomic knowledge. Finally, 39 species were recognized, both morphologically and molecularly, of which 36 are new and described. In Chapter 2, the extinct genus †Elektroepyris was revised and cladistically positioned. Morphological characters were coded, summing up to 69. The caracteres were used to perform Maximum Parsimony reconstruction, including representatives of all subfamilies of Bethylidae, extant or extinct. †Elektroepyris was recovered as a lineage distinct from other subfamilies of Bethylidae and for this reason, a new subfamily, †Elektroepyrinae, was described, based on an autapomorphy of the anterior wing with the third abscissa of the Cu vein. In Chapter 3, the paleodiversity of Epyrinae was reviewed alpha-taxonomically. Thirty extinct species of Epyrinae were recognized, distributed in six genera (Anisepyris, Chlorepyris, Epyris, †Gloxinius, Holepyris and Laelius). A new genus, †Gloxinius, has been proposed for the subfamily to allocate †G. bifossatus and two species were transferred from Epyris to 14 Chlorepyris. Three species were transferred from Epyris to Pristocerinae: †Merascylla is proposed to allocate the species †M. atavellus, and two other species are transferred to Pseudisobrachium. One species is transferred from Epyris to Scleroderminae: †Mael is proposed to allocate the species †M. longiceps. The species †Laelius nudipennis is not a bethylid and has been transferred to Platygastroidea incertae sedis. In Chapter 4, a Bayesian inference analysis was performed to reconstruct a total evidence topology from a matrix with 195 terminal taxa and 3599 characters, containing 232 morphological characters and the genes 16S, 18S, 28S, COI and Cytb. This is the first phylogenetic study that examined all 42 generic names of Epyrinae, including junior synonyms and extinct taxa. The results recovered Anisepyris, Bakeriella, Calyozina, Chlorepyris, Disepyris, Laelius, and Trachepyris as monophyletic and Formosiepyris, Epyris, and Holepyris as polyphyletic. Two new genera are proposed, GenusA to be proposed as gen. nov. and GenusB to be proposed as gen. nov., and six genera were revalidated, five junior synonyms of Epyris and one of Holepyris: Calyoza to be proposed as stat. rev., Dolus to be proposed as stat. rev., Muellerella to be proposed as stat. rev., Psilepyris to be proposed as stat. rev., Rysepyris to be proposed as stat. rev. and Trissepyris to be proposed as stat. rev. In addition, all 962 species of Epyrinae were reviewed via direct observation of the holotype, illustrations, or literature and were distributed over 17 genera: Anisepyris, Aspidepyris, Bakeriella, Calyoza to be proposed as stat. rev., Calyozina, Chlorepyris, Dolus to be proposed as stat. rev., Epyris, GenusA to be proposed as gen. nov., GenusB to be proposed as gen. nov., †Gloxinius, Holepyris, Laelius, Muellerella to be proposed as stat. rev., Psilepyris to be proposed as stat. rev., Rysepyris to be proposed as stat. rev. and Trissepyris to be proposed as stat. rev..